2015
DOI: 10.1186/s13063-015-0932-6
|View full text |Cite
|
Sign up to set email alerts
|

High frequency oscillations in the intra-operative ECoG to guide epilepsy surgery (“The HFO Trial”): study protocol for a randomized controlled trial

Abstract: BackgroundIntra-operative electrocorticography, based on interictal spikes and spike patterns, is performed to optimize delineation of the epileptogenic tissue during epilepsy surgery. High frequency oscillations (HFOs, 80–500 Hz) have been identified as more precise biomarkers for epileptogenic tissue. The aim of the trial is to determine prospectively if ioECoG-tailored surgery using HFOs, instead of interictal spikes, is feasible and will lead to an equal or better seizure outcome.Methods\DesignWe present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 41 publications
(71 reference statements)
2
57
2
1
Order By: Relevance
“…Quantifying HFO rates using iEEG recordings from the epilepsy monitoring unit or operating room has been proposed as a means to identify epileptogenic brain regions (van ’t Klooster et al, 2015a, 2015b) and studies have suggested that simultaneous HFOs and inter-ictal epileptiform spikes (IES) are stronger indicators of epileptogenic tissue than IES events alone (Jacobs et al, 2008). A major challenge in the accurate evaluation of these biomarkers is that artifacts and sharp IESs can mimic HFOs when filtered.…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying HFO rates using iEEG recordings from the epilepsy monitoring unit or operating room has been proposed as a means to identify epileptogenic brain regions (van ’t Klooster et al, 2015a, 2015b) and studies have suggested that simultaneous HFOs and inter-ictal epileptiform spikes (IES) are stronger indicators of epileptogenic tissue than IES events alone (Jacobs et al, 2008). A major challenge in the accurate evaluation of these biomarkers is that artifacts and sharp IESs can mimic HFOs when filtered.…”
Section: Discussionmentioning
confidence: 99%
“…21, 22 There is much clinical evidence of their utility, 19, 35 and a clinical trial has begun, 36 making HFOs one of the most important potential biomarkers of epilepsy. They have been shown to delineate abnormal tissue, 20, 3740 and thus have clear potential as a clinical tool to localize epileptic tissue spatially.…”
Section: Discussionmentioning
confidence: 99%
“…In order to implement the clinical use of HFOs, their value has yet to be confirmed in prospective fashion. The first small clinical trial (N=78), testing noninferiority of HFOs compared to interictal spikes during surgery, is currently being run (van 't Klooster et al , 2015a). Evidence for superiority of HFOs over spikes requires an international clinical trial with large numbers of patients, which will need fast, unsupervised and reliable automatic detection of HFOs.…”
Section: Introductionmentioning
confidence: 99%